Radioimmunoscintigraphy of ocular melanoma with 99mTc labelled cutaneous melanoma antibody fragments. Issue 9 (September 1987) - Bomanji, J.; Hungerford, J. L.; Granowska, M.; Britton, K. E.
Abstract : The possibility of using radiolabelled monoclonal antibody fragments to image uveal melanomas has been assessed in a pilot study. 99mTc labelled F(ab')2 fragments of MoAb 225.28S raised against cutaneous melanomas were used. Initially 10 patients were imaged. In five patients the clinical findings were typical of uveal melanoma. Immunoscintigraphy was positive in all five cases. In a further five patients there was doubt about the diagnosis. One was though to have a choroidal haemangioma but failed to respond to treatment and immunoscintigraphy was positive, suggesting a diagnosis of melanoma. Two patients were assigned a diagnosis of choroidal haemangioma, one of melanocytoma or possible retinal pigment epithelium carcinoma, and one of metastasis. Immunoscintigraphy was negative in all these four cases. In combination with established diagnostic tests immunoscintigraphy may have a part to play in differentiating uveal melanoma from other similar tumours.